Efektivitas Media Flipbook Berbasis Praktek Langsung Dalam Meningkatkan Keterampilan Vokasional Membuat Puding Ubi Ungu Pada Anak Tunarungu Kelas VIII di SLB N Padang Sidempuan - Nur Hayati Harahap; Fatmawati Fatmawati (Universitas Negeri Padang, 2021)
This study describes the vocational skills of making purple yam pudding in grade VIII deaf children at SLB N Padang Sidempuan, where purple yam pudding is a dessert. The purpose of this research is to find out if direct practice-based flipbook media can be effective in improving vocational skills of making sweet potato pudding in grade VIII deaf children at SLB N Padang Sidempuan. Type of research used by researchers is a type of experimental research design one group pretest-postest. The technique for data collection used by researchers is through observation to see the initial condition of learners (pretest) in making purple yam pudding, then given treatment using flipbook media based on direct practice in making purple yam pudding and the last one is (postest) to see the ability of learners in making purple yam pudding after treatment. Then the results can be processed and compared using nonparametric statistical tests using wilcoxon sign rank test with SPSS 23 program.The results of this study showed that flipbook media based on direct practice is effective in improving vocational skills in making purple yam pudding in grade VIII deaf children at SLB N Padang Sidempuan.